Penggunaan Entertainment Education Sebagai Strategi Komunikasi Instruksional Di Sekolah Kita Rumpin - Febiola Aditya Yusuf; Dewi Kurniawati (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
This study aims to determine how the use of Entertainment Education as instructional communication strategies applied in non-formal education in order to increasing the confidence of the learners. The method used in this study is qualitative method. The results of the data that obtained from in-depth interviews with informants then analyzed using Miles and Hubberman data analysis techniques. The purpose of this study is to give contribution to instructional communication studies especially with the uses of relational approach where the learners not only as receivers but also as a sources of informations at the end creates shared meanings with teachers in educational process. This is shown at the results of this study that indicate SKR teachers only act as fasilitator whereas the learners are more active to contribute to the point they freely suggest the content of study for the following weeks and choose the class as they want.